Desiminasi Pengembangan Media Pembelajaran Modul Elektronik Kimia Generasi ke-4 pada Guru Kimia di Wilayah Jakarta Timur 2 - Nurjayadi, Muktiningsih; Irma Ratna Kartika; Irwan Saputra; Siti Fatimah; Ririn Gustini; Uswatul Nisa; Rizkahana Syehfia; Nida Nur Afifah; Jefferson Lynford Declan; Pardiana; Sintia Mardita (Bahasa Indonesia, 2024)
generation electronic module is one of the chemistry learning media that can facilitate a three-way interaction between students, teachers and learning resources in 5.0 society era. Various chemical materials can be presented in the form of electronic modules equipped with applications according to the characteristics of the material. However, these developments are often not followed by the development of teacher competence in the field. So that there is a gap between scientific developments in Higher Education and conditions in the field. In this community service program, dissemination of the development of the 4th generation chemistry e-module has been carried out for MGMP-2 (Musyawarah Guru Mata Pelajaran) teachers in the East Jakarta Region through the dissemination of research results conducted in the Chemistry Education Program of FMIPA UNJ, that carried out face to face, starting with the delivery of material, Workshop, interactive discussion and coaching online blended learning. During the process of delivering the material, the participants enthusiastically followed it step by step. At the end of the session an evaluation questionnaire was given, the input and suggestions obtained were very positive. So, it is hoped that this activity can continue to be carried out and be useful in disseminating science and technology, increasing teacher competence and adding development information in tertiary institutions according to field needs. Abstrak Perkembangan teknologi sangat mempengaruhi perkembangan media pembelajaran kimia saat ini. Elektronik modul generasi ke-4 merupakan salah satu media pembelajaran kimia yang dapat memfasilitasi interaksi tiga arah antara siswa, guru dan sumber belajar di era society 5.0. Berbagai materi kimia dapat disajikan dalam bentuk modul elektronik yang dilengkapi dengan aplikasi sesuai karakteristik materinya. Namun perkembangan media pembelajaran tersebut sering tidak diikuti dengan perkembangan kompetensi guru di lapangan. Sehingga terjadi kesenjangan antara perkembangan keilmuan di Perguruan Tinggi dengan kondisi dilapangan. Pada program pengabdian pada masyakarat ini, telah dilakukan desiminasi pengembangan e-modul kimia generasi ke-4 bagi guru MGMP-2 (Musyawarah Guru Mata Pelajaran) Wilayah Jakarta Timur melalui desiminiasi hasil penelitian yang dilakukan di rumpun Kimia FMIPA UNJ yang dilakukan seacara tatap muka, dimulai dengan penyampaian materi, Workshop, diskusi interaktif dan pembinaan secara blanded learning. Selama proses penyampaian materi, peserta antusias mengikuti tahap demi tahap. Pada akhir sesi diberikan angket evaluasi, masukan dan saran yang didapat sangat positif. Sehingga diharapkan kegiatan ini dapat terus dilakuakan dan bermanfaat dalam menyebarluaskan IPTEK, meningkatkan kompetensi guru serta menambah informasi pengembangan di Perguruan Tinggi sesuai dengan kebutuhan dilapangan.